Analysis of Drinking Water Quality and Environmental Health Risks Due to Exposure to Lead (Pb), Cadmium (Cd), and Iron (Fe) at Refill Drinking Water Depots in the Work Area of the Kadolomoko Community Health Center, Baubau City - Dewi Sartika; Ramdhan Tosepu; Ridwan Adi Surya (Lembaga Pengembangan Kinerja Dosen, 2025)
Heavy mental contamination in drinking water can be toxic to the bodythis is because the metal is not needed by the body. Cadmium (Cd) and lead (Pb) are dangerous heavy metals because they cannot be broken down by the body and can accumulate in the environment, forming complex compounds at the bottom of the water while Iron (Fe) (essential metal) is needed by the body, but in excessive amounts will cause poisoning. The high use of refilled drinking water has the risk of increasing waterborne diseases. This study aims to determine the content of Lead (Pb), Cadmium (Cd), Iron (Fe) and environmental risks due to exposure to drinking water at the Refill Drinking Water Depot in the Kadolomoko Health Center area of ​​Baubau City. This study uses a descriptive observational method with a design of the Environmental Health Risk Analysis method. The population is all the number of Refill Drinking Water Depots and tested using the Atomic Absorption Spectrophotometer (AAS) method and 6497 people who consume drinking water from the Depot with samples using Slovin totaling 96 respondents with questionnaire instruments and univariate tests. The results of chemical parameters in drinking water at the Refill Drinking Water Depot in the working area of ​​the Kadolomoko Health Center are in accordance with the standard quality standards based on Permenkes No. 2 of 2023 and the results of the Intake Risk Analysis of ingestion exposure in the next 5 years, the ECR value of Lead (Pb) = mg / l / day and the RQ value of Cadmium (Cd) = 0.12 mg / l / day and Iron (Fe) = 0.00043 mg / l / day while in the next 30 years the ECR value of Lead (Pb) =mg/day and the RQ value of Cadmium (Cd) = 0.12 mg/l/day and Iron (Fe) = 0.0004 mg/l/day does not exceed the quality standard, namely ECR ≥ E-4 (10-4) and RQ ≥ 1 Conclusion Refill drinking water at the depot in the Kadolomok Community Health Center work area is safe for consumption for up to 5 years and 30 years into the future.